Microvascular perfusion changes in the posterior segment of the eye in patients after cataract removal by phacoemulsyfication - Nowak, Mateusz (2021)
The aim Getting the answer to the question of whether ultrasound during uncomplicated surgery to remove the carom has an effect on changes in retinal microcirculation with angino-OCT. Method Patients qualified for cataract removal by phacoemulsification were recruited at the 5th Military Clinical Hospital. A retinal microcirculation test was performed before surgery, 7 days, 30 days and 5 months after uncomplicated surgery. Results 60 patients met the inclusion criteria. In the study group there was a significant increase in retinal microcirculation parameters, such as: perfusion density, vessel density and retinal thickness. A statistical study excluded the effect of ultrasound on changes in retinal microcirculation and the effect of ultrasound on final, postoperative and corrected visual acuity in patients without retinal disease, as well as postoperative changes in FAZ parameters. In the study group, an increase in the length of vessels was observed without changing their average diameter remaining in a very narrow range of 17.9-18.5 μm. Conclusions Perfusion density, vessel density, and retinal thickness increased after uncomplicated cataract surgery. The increase in retinal microcirculation parameters was not due to intraoperative use of ultrasound. What mechanism causes their increase and whether the parameters will persist is the goal of further scientific wo
Keywords: zaćma; fakoemulsyfikacja; mikrokrążenie siatkówkowe; angiografia OCT